О постэндодонтической реставрации зубов (Эндодонтия Today, 2020)
Clinical cases of post endodontic restoration techniques of teeth with defects of more than ½ the crown volume are presented. In order to improve the adhesion, strength and the aesthetic aspects of the restoration the polymer fiber ribbon was used. High cosmetic level of the restoration was observed.